2015
DOI: 10.1002/jcc.24228
|View full text |Cite
|
Sign up to set email alerts
|

Spin‐orbit ZORA and four‐component Dirac–Coulomb estimation of relativistic corrections to isotropic nuclear shieldings and chemical shifts of noble gas dimers

Abstract: Hartree-Fock and density functional theory with the hybrid B3LYP and general gradient KT2 exchange-correlation functionals were used for nonrelativistic and relativistic nuclear magnetic shielding calculations of helium, neon, argon, krypton, and xenon dimers and free atoms. Relativistic corrections were calculated with the scalar and spin-orbit zeroth-order regular approximation Hamiltonian in combination with the large Slater-type basis set QZ4P as well as with the four-component Dirac-Coulomb Hamiltonian us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 86 publications
6
16
1
Order By: Relevance
“…Evidently, the isotropic hyperfine coupling constant changed only slightly but in a consistent manner when the basis set was increased by using the DKS method and Dyall's basis sets, whereas we observed the same irregular, no‐monotonic behaviour of the ZORA basis sets, as seen previously, for nuclear magnetic shielding 31, 32. It was shown there, that the increasing cardinal number and the increasing amount of polarization functions have opposite effects, which lead to an oscillating and not yet converging behaviour.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Evidently, the isotropic hyperfine coupling constant changed only slightly but in a consistent manner when the basis set was increased by using the DKS method and Dyall's basis sets, whereas we observed the same irregular, no‐monotonic behaviour of the ZORA basis sets, as seen previously, for nuclear magnetic shielding 31, 32. It was shown there, that the increasing cardinal number and the increasing amount of polarization functions have opposite effects, which lead to an oscillating and not yet converging behaviour.…”
Section: Resultssupporting
confidence: 88%
“…For example, previous studies showed that, in ZORA calculations of nuclear magnetic shielding constants, it was important to use the large QZ4P basis sets 31, 32. Therefore, we also studied the basis set dependence of both the ZORA and DKS results for the hyperfine coupling constants in both ions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3 He NMR spectral range is moderate. Very small chemical shift is observed for helium in He 2 and benzene‐He dimers . In the latter complex, the spherical helium atom is located 3.6 Å from the middle of benzene ring and exhibits only relatively small change of its nuclear shielding with respect to free atom .…”
Section: Introductionmentioning
confidence: 95%
“…It is well established that relativistic and spin orbit effects strongly contribute to computed σ iso 195 Pt magnetic shielding tensor elements of Pt(II) and Pt(IV) coordination compounds, but this contribution is effectively canceled in the computed δ 195 Pt chemical shifts with respect to the reference standards, because the relativistic corrections are expected to be similar in the complexes and the reference standards. Very recently, Jankowska et al studying systematically the importance of relativistic effects for the noble gas nuclear shielding and the He 2 ‐Xe 2 noble gas dimers chemical shifts showed that for the chemical shifts of the noble gas dimers, the relativistic corrections almost cancel.…”
Section: Introductionmentioning
confidence: 99%